2014
DOI: 10.1179/1432891714z.000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Research on new type MRE isolator and its mechanical model

Abstract: A new type of seismic isolator with adjustable stiffness is proposed, based on the smart material of magnetorheological elastomers (MREs). This paper specifies the working principle of the isolator, analyses magnetic induction distribution of three different types of MRE isolators, which are unicoil magnetic energy input, twin coil magnetic energy input, and laminated steel plate coiling magnetic energy input respectively. The research shows that the third type of input produces relatively greater magnetic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The element is used within the tunable stiffness device or compliance is needed to be experimentally characterized under the compression test. [112] controllable flux in compression status of MREs has also been introduced by several researchers in quasi-static compression, [45] and quasi-dynamic compression [48,[198][199][200][201] in which various flux densities applied during characterization. The compression test was performed by Farshad and Benine [11] using a displacementcontrolled compression machine by adding a permanent magnet (certain flux density).…”
Section: Mechanical Properties Testmentioning
confidence: 99%
“…The element is used within the tunable stiffness device or compliance is needed to be experimentally characterized under the compression test. [112] controllable flux in compression status of MREs has also been introduced by several researchers in quasi-static compression, [45] and quasi-dynamic compression [48,[198][199][200][201] in which various flux densities applied during characterization. The compression test was performed by Farshad and Benine [11] using a displacementcontrolled compression machine by adding a permanent magnet (certain flux density).…”
Section: Mechanical Properties Testmentioning
confidence: 99%
“…It is seen that the prototype mainly consists of MRE-steel laminates, a coil, steel yokes and silicon steel sheets. There are 10 2 mm thick-MRE layers in the MRE-steel laminates, with the radii of 25,27,29,31,33,35,37,38,39, and 40 mm from the top to the bottom, respectively. The parameters of the cylindrical electromagnetic coil are listed in table 1.…”
Section: The Mre Isolator To Be Modeledmentioning
confidence: 99%
“…Li [34] built a finite element electromagnetic model to provide sufficient and uniform magnetic field. Tu [35] built electromagnetic models for three different types of MRE isolators, and obtained the magnetic field distributions in MRE layers.…”
Section: Introductionmentioning
confidence: 99%
“…A design methodology was presented for an MRE base isolator by Yang et al (2014Yang et al ( , 2015 that incorporates a permanent magnet and can achieve both positive and negative stiffness changes based on the direction of the applied magnetic field. Tu et al (2014) investigated the field-dependent shear modulus of an MRE isolator and concluded that the shear modulus increases 40% before reaching magnetic saturation. Xing et al (2015) designed and tested the performance of a bridge bearing using MRE layers and implemented a field-dependent model to consider the dependency of the stiffness and damping of the isolator on the applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%